FUNCTIONAL CHARACTERISTICS OF ANTHROPONYMS IN O‘TKIR HOSHIMOV’S SHORT STORY “UZUN KECHALAR” - S.B.Khursankulov; D.Z.Abduazimova (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This article provides a systematic analysis of the linguopoetic features of anthroponyms used in O‘tkir Hoshimov’s short story “Uzun kechalar.” The study examines the functional-semantic characteristics of personal names found in the literary text, as well as their role in revealing character traits, reflecting the social environment, and expressing the author’s intent. In addition, the aesthetic and semantic load of anthroponyms within the text is identified, and their functions as a means of artistic expression are interpreted on a scientific basis. The results of the research demonstrate that anthroponyms function not only as nominative units but also as significant linguistic and artistic components.